DEVELOPING READING ASSESSMENT INSTRUMENT FOR INTERMEDIATE EFL LEARNERS: AZWAR MODEL - Masitoh, Fitriatul; Fitriyah, Ima; Mukminatien, Nur (University of Kuningan, 2023)
The study was inspired by the fact that teachers of an intermediate English reading course employed a pre-made reading instrument particularly tests obtained from the internet, the TOEFL, or a textbook without consulting the learning objectives. Therefore, they cannot meet the demand of the teaching and learning objectives and the classroom-based assessment that should be tailored to the unique circumstances of the course. The objective of this study is to create intermediate reading comprehension test items for EFL students that adhere to the